The man who never was [videorecording (DVD)] - Neame, Ronald; Webb, Clifton, 1889-1966; Montagu, Ewen, 1901-1985 (Twentieth Century Fox Home Entertainment, 2005)
Account of wartime espionage based on the true story of an intelligence operation designed to mislead the Nazis prior to the 1943 Allied invasion of Sicily.